Numerical thermal featuring in γAl2O3-C2H6O2 nanofluid under the influence of thermal radiation and convective heat condition by inducing novel effects of effective Prandtl number model (EPNM). (June 2022) - Adnan; Ashraf, Waqas
The investigation of thermal transport in the nanofluid attained much interest of the researchers due to their extensive applications in automobile, mechanical engineering, radiators, aerodynamics, and many other industries. Therefore, a nanofluid model is developed for γAl2 O3 -C2 H6 O2 by incorporating the novel effects of Effective Prandtl Number Model (EPNM), thermal radiations, and convective heat condition. The model discussed numerically and furnished the results against the governing flow quantities. It is examined that the nanofluid velocity alters significantly due to combined convection and stretching parameter. Induction of thermal radiation in the model significantly contributed in the temperature of nanofluids and high temperature is observed by strengthen thermal radiation (Rd) parameter. Further, convection from the surface (convective heat condition) provided extra energy to the fluid particles which boosts the temperature of γAl2 O3 -C2 H6 O2 . The comparison of nanofluid (γAl2 O3 -C2 H6 O2 ) temperature with base fluid (C2 H6 O2 ) revealed that γAl2 O3 -C2 H6 O2 has high temperature and would be fruitful for future industrial applications. Moreover, the study is validated with previously reported literature and found reliability of the study.